(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2026)
This study examines the structure and interpretation of possessive noun phrases in Malay from both morphosyntactic and pragmatic perspectives. It focuses on three principal possessive constructions: the N + N construction (e.g., rumah saya [my house], basikal saya [my bicycle]), the clitic-nya construction (e.g., basikalnya [his/her bicycle], rumahnya [his/her house]) and the lexical possessive marker punya (own). The analysis is based on corpus data extracted from the Dewan Bahasa dan Pustaka (DBP) corpus database, providing empirical evidence of naturally occurring possessive usage in Malay discourse. A total of 338 concordances of basikalnya and 100 concordances of rumahnya were generated from texts across all genres and decades. For the N + N possessive pattern, 259 relevant concordances were identified from the first 2,000 corpus hits of the structure exemplified by rumah saya, as documented in Tatabahasa Dewan. In addition, data on the lexical marker punya were extracted, yielding 14,393 concordances from the DBP corpus, reflecting its widespread use in possessive constructions. Methodologically, the study employs a morphological-syntactic analysis grounded in transformational generative grammar, drawing on the Minimalist Program to account for the internal composition and syntactic derivation of possessive noun phrases. While this structural analysis captures the formal properties of possession, it does not fully explain how Malay speakers interpret possessive meaning in constructions lacking overt genitive morphology. To address this, the study incorporates Relevance Theory as a pragmatic analytical framework, highlighting the role of inferential processes, contextual assumptions and cognitive optimisation in meaning interpretation. The findings show that Malay speakers systematically recover possessive meaning through pragmatic inference, relying on contextual cues and shared knowledge even in the absence of explicit morphological marking. This study contributes to the understanding of Malay morphosyntax and pragmatics by elucidating how possession is structurally represented and cognitively inferred in a language without overt genitive marking.